The role of mixed emotions in language learning and teaching: A positive psychology teacher intervention. (July 2022) - Alrabai, Fakieh
Abstract: This study adopted a quasi experimental design to examine the impact of a pedagogical positive psychology (PP) intervention on how the integration of positive and negative emotions in English as a foreign language (EFL) learning and teaching affects learner language motivation as a positive affective variable, anxiety as a negative emotion, and EFL achievement as a learning outcome. To address this question empirically, the study implemented three emotion-regulation quasi experiments employed by 6 EFL teachers with 209 EFL learners divided into three groups for 12 weeks: in group 1, learners were exposed extensively to anxiety-regulating strategies, those in group 2 were thoroughly exposed to motivation-promoting strategies, and those in group 3 were exposed to combined anxiety-regulating and motivational strategies together. The influence of the treatment was assessed using questionnaires, classroom observations, and achievement tests. ANOVAs and MANOVAs were employed to capture treatment effects. The findings show that integrating positive and negative emotions in language learning resulted in the largest positive change in learner's motivation, anxiety, and language achievement. These findings support the assumptions of the Broaden-Build Theory in that positive emotions not only broaden people's vision and build strengths but further help undo the lingering effects of negative emotions.